Sulfonated (1→6)-β-d-glucan (lasiodiplodan) : preparation, characterization and bioactive properties - Calegari, Gabrielle Cristina (Array, 2019)
Sulfonated derivatives of lasiodiplodan (LAS-S) with different degrees of substitution (1.61, 1.42, 1.02 and 0.15) were obtained and characterized by Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and thermal and solubility analyses. Antimicrobial, antioxidant and cytotoxic potential were also assessed. The sulfonation was confirmed by FTIR analysis with specific bands at 1250 cm–1 (S=O, strong asymmetrical stretching vibration) and at 810 cm–1 (C-O-S, symmetrical vibration associated with the C-O-SO3 group) in the sulfonated samples. SEM demonstrated that sulfonation promoted morphological changes on the surface of the biopolymer with heterogeneous fibrillary structures appearing along the surface following chemical modification. LAS-S showed high thermal stability, with mass loss due to oxidation at temperatures close to 460 °C. Sulfonation increased the solubility of LAS, and in addition, increased the antimicrobial activity, especially against Candida albicans (fungicidal) and Salmonella enterica Typhimurium (bacteriostatic). Native lasiodiplodan (LAS-N) showed higher OH˙ removal capacity, while LAS-S had higher ferric ion reducing antioxidant power (FRAP) potential. LAS-N and LAS-S did not demonstrate lethal cytotoxicity against wild and mutant strains of Saccharomyces cerevisiae. Samples with higher degree of substitution (1.42 and 1.61) showed lower potential to induce oxidative stress.